The Influence of Faith: Religious Groups and U.S. Foreign Policy - Abrams, Elliott, (Rowman & Littlefield Publishers, 2002)
Realists have long argued that the international system must be based on hard calculations of power and interest. But in recent years, religion's role on the international scene has grown. The Influence of Faith examines religion as a growing factor in world politics and U.S. foreign policy. Particular attention is placed on the American reaction to the persecution of Christians and Jews overseas, as well as the role of faith-based groups such as missionary and relief organizations in the formulation and implementation of U.S. policy. The Influence of Faith considers these timely issues from diverse points of view, offering broad historical analysis as well as concrete examples taken from current affairs.